2021
DOI: 10.1371/journal.pone.0247492
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer effects of polyphenol-rich sugarcane extract

Abstract: Plant polyphenols have an array of health benefits primarily thought to be related to their high content of anti-oxidants. These are commonly undervalued and knowledge of their biological properties have grown exponentially in the last decade. Polyphenol-rich sugarcane extract (PRSE), a natural extract from sugar cane, is marketed as high in anti-oxidants and polyphenols, but its anti-cancer activity has not been reported previously. We show that, PRSE exerts anti-cancer properties on a range of cancer cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…The anti-cancer properties of natural plant-derived antioxidants have been demonstrated in vitro in relation to various cell lines of breast, skin, colon, prostate, lung and bladder cancers and leukemia [ 13 , 14 , 15 ]. Acting as bioactive compounds, the polyphenols affect the process of the expression of many genes, and the molecular mechanism of their action is mainly associated with the redox homeostasis of cells, inflammation, the cell cycle and the apoptosis regulation and modulation of the essential cell signaling pathways [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-cancer properties of natural plant-derived antioxidants have been demonstrated in vitro in relation to various cell lines of breast, skin, colon, prostate, lung and bladder cancers and leukemia [ 13 , 14 , 15 ]. Acting as bioactive compounds, the polyphenols affect the process of the expression of many genes, and the molecular mechanism of their action is mainly associated with the redox homeostasis of cells, inflammation, the cell cycle and the apoptosis regulation and modulation of the essential cell signaling pathways [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-proliferative effects were shown to be mediated via alteration in cytokines, VEGF-1 and NF-κB expression. 28 Rubin-Garcia et al showed that a diet high in polyphenol compounds like stilbenes, lignans, hydroxybenzaldehydes, hydroxycoumarins, and tyrosols was associated with a lower gastric cancer risk. 29 Olive oil polyphenols (OOPs), especially hydroxytyrosol (HTyr), tyrosol (Tyr) and their derivatives oleuropein (Ole), express anticancer activity on different cancer models.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were processed for downstream analysis after 24 h in culture. PRSE at 400 µg/mL was chosen based on previous in vitro experiments on modulation and anti-inflammatory effects of cancer cell lines [27]. All analyses were performed on three technical replicates, and with sample means presented.…”
Section: Treatment Groupsmentioning
confidence: 99%
“…It is also able to impart benefits in diabetes, has anti-bacterial effects and improves the cosmetic effects of aging in the skin [25]. PRSE has also been shown to modulate the immune system, with effects on inflammation, cancer and neurological disorders [26,27].…”
Section: Introductionmentioning
confidence: 99%